Pelatihan Peningkatan Literasi melalui Permainan Edukatif pada Anak Lingkungan Tamo Dhua - Arifin, Sartika; Aprisal, Aprisal; Nurhidayah, Nurhidayah; Adinang, Adinang; Muliadi, Aldi; Hasrat, Muh (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
. Literacy improvement training in both reading and arithmetic with educational games for children in the Tamo Dhua neighborhood, Majene Regency, will be held in June - July 2023. The activity begins with initial observations to find out real data on the literacy skills of children in the Tamo Dhua neighborhood, Majene Regency, then holding numeracy training with educational games, reading training with educational games as well as providing an evaluation in the form of a rating of 1 to determine the ability of participants after being given training. The results obtained are that children are enthusiastic and active in receiving the material provided. Children who initially could not recognize letters and numbers, after attending the training were able to recognize letters and numbers and some even could read or count.